(untitled) (Bangladesh Journal of Pharmacology, 2017)
Seventy-two females with mild to moderate knee osteoarthritis were included in this randomized double-blind placebo-controlled study. Patients in the intervention group (n=36) received L-carnitine supplement (750 mg/day) for two months. L-Carnitine supplementation led to decrease in serum TNF-? and MMP-3 levels significantly in comparison with the baseline (p<0.001 and p<0.001, respectively) and placebo group (p<0.001 and p=0.03, respectively). In addition, physicians global assessment of the severity of osteoarthritis decreased significantly in the L-carnitine group (p<0.001) and placebo group (p=0.012) after supplementation. At the end of the study, a significant difference was observed between the two groups for mean physicians global assessment of the severity of osteoarthritis (p<0.001), adjusted for baseline values and duration of osteoarthritis. L-Carnitine supplementation has beneficial effects in reducing inflammatory biomarkers in knee osteoarthritis patients which subsequently leads to the alleviation of disease symptoms.